Kajian Penurunan Kadar BOD Limbah Cair Tahu Pada Berbagai Variasi Aliran - Hendrasari, Ratna Septi (Semesta Teknika, 2016)
Tofu is a food that derived from soybeans that have been fermented and taken juice. Tofu is a favored food of the community because of high nutritious and cheap. As a result, many emerging industries making tofu where this activity will produce liquid waste. Tofu liquid waste contains some substances including BOD. High BOD levels should not be directly disposed into the river. Therefore before the waste disposed, the levels of BOD should be reduced in accordance with the quality standards of waste. Decreased levels of BOD can be done in several ways such as by the waste stream in a stream. On the various streams will have different flow characteristics. The flow variation among others stepping on a sudden waterfall and stepping on the sudden expansion. Variations in flow was analyzed using the equations of continuity and momentum. The sample of liquid waste taken from the industrial society in Srandakan Bantul. From the results obtained in the laboratory testing, levels of BOD is 5571 mg/L. The study was conducted by assuming a square-shaped channel with a channel width of 0.2 m and a flow of 1 m3/s. The study was conducted by assuming a square-shaped channel with a channel width of 0.2 m and a flow of 1 m3/s. From the results of the study showed that the percentage reduction in BOD in liquid waste that declined most for the Froude number from 2 to 8 are on Î”Z/ h1 = 0.8 ie from 0.0134% to 0.0237%Â  and the b/B = 0.4 ie from 0.0589% to 0.0733%. BOD levels of liquid waste that has experienced a hydraulic stepping on a waterfall as well as the expansion of a sudden, for the Froude number from 2 to 18 in a row is 5569.916693 mg/L to 5569.779468 mg/L and 5566.916554 mg/L until 5570.999943 mg/L.